MEREFLEKSIKAN SAINS UNTUK ECOTEOLOGI Telaah Pemikiran Pierre Teilhard de Chardin dan Robert Spitzer - Christoforus Bayu Risanto (P3TK, Sanata Dharma University, 2013)
This writing is an attempt to discuss an ecotheology from the scientific point of view. The main sentence is that reflecting on the development of science which has ecological impacts could bring human beings to the awareness of their own lives, their relation with nature, and Gods presence in nature. The thoughts of two great minds, namely of Teilhard de Chardin and Robert Spitzer are being considered here and help reflect on the progress of science, mainly physics, chemistry, and biology in order to build this scientific-based ecotheology. This reflection holds its importance in todays world as we face ecological catastrophes. The culprit is humans voracity of energy to develop their lives, mainly in economic basis. Science that primarily serves human knowledge to search and find out the unknown regions of the universe is also able to serve the development of technology especially which generates energy. Since then, human beings exploit the sources of energy such as crude oil, coal, natural gas, and uranium, and in doing so they destroy Mother Nature and foul her with poisonous wastes.